ANALISIS KOMPARATIF : MENGEKSPLORASI DAMPAK AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN: Akuisisi, Kinerja Keuangan, Rasio Keuangan - Dina Ekasari, Luh; As’adi, As’adi; Fitria Hayuningtyas, Ruri; Himawan Wibisono, Sukarno (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The increasingly fierce competition in the business world requires all companies to survive in every condition and be able to compete with other companies. One of the ways that needs to be done is by making acquisitions. The purpose of this research is to determine the impact of acquisitions on financial performance. In this study using descriptive analysis techniques, namely analysis techniques by collecting data, explaining and analyzing so as to provide information according to the problems faced. The results of the study show that only the current ratio and debt to equity ratio provide changes in the company's financial performance after the acquisition. while the ratio of return on assets and total asset turnover does not change the company's financial performance after the acquisition